The results of determining the indicators of the morphological composition of the blood of animals and individual biochemical indicators using a potential drug with a mixture of two active compounds: 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine and 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol in milk thistle seed oil - M. V. Ohloblina; I V. Bushuieva; V. V. Parchenko (Zaporozhye State Medical University, 2022)
The introduction of new domestic highly effective and safe medicines into medical and veterinary practice is an important task of modern pharmaceutical science. Continuation of the search and conduct of research to bring the biological activity of 1,2,4-triazole derivatives is one of the promising areas of such activity. At this stage of research, it is known that such 1,2,4-triazole derivatives as 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine and 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol have a wide spectrum of biological activity. Interest for further thorough research is precisely the antimicrobial and antifungal effects. The introduction into medical and veterinary practice of newly created drugs for the treatment of fungal diseases on the skin of animals requires further studies of the properties of these compounds and their mixtures. The aim of the work was to determine the indicators of the morphological composition of the blood of animals and individual biochemical indicators when using a preparation with a mixture of two active compounds: 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine and 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol in thistle seed oil. Materials and methods. The material for laboratory research was serum and blood plasma, stabilized by adding trilon-B, tissue biopsy. Indicators were determined in healthy animals and experimentally diseased animals on the third and tenth days after the onset of the disease according to the generally accepted method. During the research, in the course of treatment, general clinical examinations and local examinations of purulent wounds were carried out, as well as blood samples taken from each head of the sheep in the experimental and control groups before the beginning and on the third and tenth days of the experiment. The purulent-inflammatory process was caused by injuring the soft tissues in the groin area on the left side, with the help of a specially made template, followed by dilation of the muscle tissue with an angiotrip and implantation of aerobic-anaerobic surgical infection cultures taken from the bed. The resulting wounds had the following dimensions: 10 cm in length, 1 cm in width, and 2 cm in depth. As early as 24 hours after induction of experimental purulent inflammation, characteristic clinical signs appeared in sheep. The general condition of all 12 animals was somewhat depressed, the appetite was normal. The body temperature was in the range of 38.6-40.3 °C, the pulse was 76-82 beats, and the frequency of respiratory movements was 16-18 per minute. The frequency of scar contractions was 3-6 times in 2 minutes. During the examination, slight swelling was also found in the area of the wound and its edges. There was a small amount of serous-bloody exudate on the surface of the wound. On the 3rd day, the maximum manifestation of clinical signs of acute purulent inflammation was observed in all 12 sheep. In particular, the general condition of the animals is depressed. A partial loss of appetite was observed. General temperature 40.4-40.8 °C, pulse 75-82 beats, frequency of respiratory movements 18-22 per minute. The frequency of scar contractions was 3-6 times in 2 minutes. Visible mucous membranes are pale pink in color. When pressing on the area of the wound, a serous-purulent exudate was observed. Results. Laboratory indicators of blood and tissue biopsy that are more optimal than in the control group confirm positive changes in the clinical status of the animals in the experimental group. The use of a potential preparation with a mixture of two active compounds: 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine and 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol in thistle seed oil leads to faster healing of purulent wounds, in relation to the use of "Vetmikoderm" liniment (control group). The difference in the areas of the wound defect on the 10-11th day was 17.5 %. Clinical studies were confirmed by laboratory studies and wound biopsies. Conclusions. The preparation with two compounds: 4-((5-(decylthio)-4-methyl-4H-1,2,4-triazole-3-yl)methyl)morpholine and 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol had pronounced pharmacokinetic parameters and was bioavailable.